Energy analysis of a detonation combustor with a bladeless turbine, a propulsion unit for subsonic to hypersonic flight. (15th June 2022) - Braun, James; Falempin, Francois; Paniagua, Guillermo
Highlights: Cycle analysis of the bladeless turbine for supersonic propulsion. First demonstration of coupling rotating detonation combustor to bladeless turbine. A comprehensive demonstration of the operability of the bladeless turbine. Abstract: This paper details an energy conversion unit for the combined power extraction and thrust increase from high subsonic to hypersonic flows. The energy transfer is achieved through a wavy hub surface that promotes shocks and expansion fans. First, a design procedure and the non-dimensional steady-state performance characteristics (the reduced torque, non-dimensional mass flow, and non-dimensional speed) are presented (including an exergetic analysis) at on– and off-design conditions through time-averaged Reynolds Averaged Navier Stokes simulations. A cycle analysis was performed on a Mach 3 vehicle to demonstrate the feasibility of this technology. Second, energy extraction is achieved from the highly unsteady exhaust of rotating detonation combustors without needing an additional intermediate diffuser or nozzle. The rotating boundary conditions were computed from a reactive unsteady simulation. The influence of three shock parameters (pressure ratio across the shock, shock wave Mach number, and the number of waves) is investigated through a sensitivity study to assess the robustness of the new device. Furthermore, depending on the sense of rotation of the bladeless turbine relative to the rotation of the incoming shock and the helix angle, we can define two different modes of operation in which power extraction was achieved, namely, the shock mode and reversed mode.